Gain Enhancement of Double-Slot Vivaldi Antenna using Corrugated Edges and Semicircle Director for Microwave Imaging Application - Findi Nur Witriani; Yahya Syukri Amrullah; Fajri Darwis; Taufiqqurrachman Taufiqqurrachman; Yusuf Nur Wijayanto; Ken Paramayudha; Elisma Elisma (LIPI Press, 2021)
Microwave imaging, such as images for radiological inspection in the medical profession, is one of the applications utilized in ultra-wideband (UWB) frequency ranges. The Vivaldi antenna is one of the most popular antennas for this purpose. The antenna is utilized because of its simple, lightweight, and compact design, as well as its excellent efficiency and gain capabilities. In this work, we present a high-gain Vivaldi antenna for microwave imaging applications. The proposed Vivaldi antenna is designed using a double-slot structure method with the addition of corrugated edges and a semicircle director aimed at improving the gain. The antenna is designed to operate at frequencies ranging from 3.1 to 10.6 GHz. Based on the modeling findings, the suggested antenna attain a bandwidth of 7.5 GHz with operating frequencies from 3.1 GHz to 10.6 GHz for a VSWR of less than two. In comparison to a typical single slot antenna, the suggested antenna provides a substantial boost in gain performance. The increase in gain is proportional to the frequency of operation. The constructed antenna has a lower bandwidth than the simulated one, with operating frequencies of 3.5 GHz – 3.75 GHz and 4.25 – 10.89 GHz, respectively, and useable bandwidths of 250 MHz and 6.64 GHz. All these results suggest that the antenna is suitable for microwave imaging applications.